Sustainability annual report 2016 - Zedillo Velasco, Carlos (Infonavit, 2017)
This report provides the opportunity to present the activities and accomplishments of the organization in general and the Research Center for Sustainable Development (CIDS) in particular, founded following the proposal of our current General Director, with the aim of investigating and recommending strategies and mechanisms regarding housing quality, quality of life and equity value with a social approach.